Implementasi Program Literasi dalam Meningkatkan Minat Belajar Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam di MTs. Darul Ulum Waru Sidoarjo - Anam, Muhammad Choirul; Sulaiman, M.Sholehuddin; El-Yunusi, M. Yusron Maulana (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2025)
Islamic religious education is one of the important roles in the progress of the nation. The literacy program is one of the keys to student success in the learning process, especially in the subject of Islamic cultural history. At MTs Darul Ulum Waru Sidoarjo, the challenges in learning Islamic cultural history are the low understanding explained by the teacher and the low interest of students. This study aims to determine the learning interest that is improved in MTs students. Darul Ulum Waru Sidoarjo To find out the implementation of the reading literacy program in increasing student interest in learning at MTs Darul Ulum Sidoarjo To find out the supporting and inhibiting factors for the implementation of the reading literacy program in increasing student interest in learning at MTs Darul Ulum Sidoarjo. This research uses a qualitative method with a descriptive approach. Data collected through observation, interviews and documentation. The results of this study indicate that the literacy program implemented at MTs. Darul Ulum Waru Sidoarjo, carried out through several activities such as reading and writing habits carried out every Monday and once a month, developing a culture of literacy by providing a mini library in each class. The results also show that the literacy program is effective in increasing students' interest in learning the subject of Islamic cultural history with the activities of reading books, writing, discussion and presentation related to the subject of Islamic cultural history. This is evidenced by the increase in student participation in learning takes place, student learning outcomes have increased and the emergence of curiosity and enthusiasm of students in studying the history of Islamic culture.